Effect of a Prescription Drug Monitoring Program on Emergency Department Opioid Prescribing - Gupta, Rahul (West J Emerg Med, 2021)
INTRODUCTION: Our goal was to determine whether implementation of a prescription drug monitoring program (PDMP) altered emergency department (ED) opioid prescription rates overall and in patients of different pain severities. METHODS: We conducted this single-center, retrospective review at an academic ED. The study examined patients discharged from the ED who received opioid prescriptions, before and after the state’s implementation of a PDMP (August 25, 2016). The monthly rate was a ratio of the patients given ≥ 1 opioid prescription to the ED patients with a numeric pain rating scale (NPRS) > 0. We performed an interrupted time series analysis on each demographic. RESULTS: The overall ED opioid prescription rate decreased from 51.3% (95% confidence interval [Cl], 50.4%–52.2%) to 47.9% (95% Cl, 47.0%–48.7%). For males, this decreased from 51.1% to 46.7% (P < 0.0001), while in females it did not significantly change (51.6% to 49.7% [P = 0.0529]). For those with mild pain, the rate increased from 27.5% to 34.3% (P < 0.0001), while for those with moderate pain, it did not significantly change (42.8% to 43.5% [P = 0.5924]). For those with severe pain, the rate decreased from 66.1% to 59.6% (P < 0.0001). CONCLUSION: We found that PDMP implementation was associated with an overall decrease in opioid prescription rates, and that patients with mild pain were prescribed opioids more often while severe pain patients were prescribed opioids less often.